2007
DOI: 10.1002/elps.200600815
|View full text |Cite
|
Sign up to set email alerts
|

In‐column fiber‐optic laser‐induced fluorescence detection for CE

Abstract: A highly sensitive in-column fiber-optic LIF detector for CE has been constructed and evaluated. In this detection system, a 457-nm diode-pumped solid-state blue laser was used as the excitation light source and an optical fiber (40 mum od) was used to transmit the excitation light. One end of the optical fiber was inserted into the separation capillary and was in situ positioned at the detection window. The other end of the fiber was protruded from the capillary to capture the excitation light beam from the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…To avoid these shortcomings, an optical fiber was inserted directly into the tail end of capillary and was settled right at the detection window in the new CE-LIF detection system. The excitation light was guided into the capillary directly and then could be utilized completely to excite analytes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these shortcomings, an optical fiber was inserted directly into the tail end of capillary and was settled right at the detection window in the new CE-LIF detection system. The excitation light was guided into the capillary directly and then could be utilized completely to excite analytes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The in-column fiber-optics LED-IF for CE has been previously described. 25,27,28 To further improve the design, a fiber coupling device was used to match the precision translation stage (Fig. 1a) with the optical fiber.…”
Section: Apparatusmentioning
confidence: 99%
“…Recently, our research group has successfully developed in-column optical fiber induced-fluorescence detection system for capillary electrophoresis (CE) [16][17][18][19][20][21][22][23][24][25]. For the in-column optical fiber induced-fluorescence detection system, our previous work demonstrated that an excitation light beam waveguided by an optical fiber to the detection point of the capillary shows relatively lower background light than that obtained from an excitation light beam impinged orthogonally on the capillary exterior wall.…”
Section: Introductionmentioning
confidence: 97%